ANALISIS PARTISIPASI MASYARAKAT LOKAL DALAM PENGEMBANGAN DESA WISATA NGLANGGERAN - Wijaya, Lilik; Maryunani (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Nglanggeran is a village with natural resource potentials that are used for tourism. However, the villages human and natural resources have not been used optimally. The objective of this research is to identify factors that enhance participation, the type of public participation in the development and the activities of Nglanggeran tourism village, and ways to develop the said tourism village. The data of this descriptive research was harvested through structured interviews, observations, and questionnaires distributed to 88 locals participating in the development of the village and was analyzed using descriptive statistical analysis. This study finds that labor participation is dominant in the development of Nglanggeran tourism village. The village has opened business opportunity for its people, but they cannot take the chances due to the lack of capital. Furthermore, the village is very likely to succeed as a tourism village since it has sufficient tourist attractiveness and infrastructures.